Historical thought and Heidegger's 'Black Notebooks': Historical thinking and hermeneutical keys of the mysterious texts 'Black Notebooks' by Martin Heidegger: Neopaganism of nietzsche and a nazi-orientation are no more the condition of philosophising - Petrović Aleksandar M. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2022)
The growing discussions of Heidegger's opus postumum, Schwartze Hefte, require adequate considerations of the issue. These discussions can no more be considered by separating Heidegger's political and philosophical thought, as was the case until now, because the content they provide is almost unambiguous. The concept of 'decision' is actualized almost universally, hence the decisionism here accounts for the negative unity of all investigating categories. We postulate that this resulted from abandoning the critical attitude and the subsequent dialectological discussion of the original ontological concepts, as well as its hermeneutical consequences. The absurdity of turning a blind eye to the glorification of Neo-Nazi inclinations should not be a part of philosophy.